Dogmatik - Härle, Wilfried (De Gruyter Studium, 2012)
A textbook for students of theology, exam preparations, and all those seeking a systematic grasp of applied dogmatics in church and school. The discipline of dogmatic theology describes the central creeds of Christianity and examines the truth of the Christian understanding of God and the world. It strives for clarity in terminology, continuity with biblical and church traditions, and mediation between thought and experience in present-day life. Wilfried Härle, Ruprecht-Karls-Universität Heidelberg.